PHYTOCHEMICAL SCREENING AND ANTIMICROBIAL ACTIVITY OF FIVE MEDICINAL PLANTS AGAINST MYROTHECIUM SP - SWADHINI S.P.; SANTHOSH R; UMA C; SATHIAVELU A. (International Journal of Pharma and Bio Sciences, 2011)
Medicinal plants are various plants thought by some to have medicinal properties, but few plants or their phytochemical constituents have been proven by rigorous science to have medicinal effects. Phytochemicals are non-nutritive plant chemicals that have protective or disease preventive properties. The main objective of the study is to isolate and identify the organism present in the infected bitter gourd leaves with NCBI BLAST homology and it was identified as organism belonging to Myrothecium sp., (Accession no. HM219863). Five medicinal plants, viz Indigofera tinctoria, Piper nigum, Curcuma longa, Polygala elongata and Polygala glabra in different solvent extracts are used in this study shows a good control to the growth of fungi Myrothecium sp., and all the five medicinal plants extracts were screened for their phytochemical content. Qualitative phytochemical tests were used to detect the presence of alkaloids, tannins, saponins, flavonoids, glycosides and phenols. Presence of these phytochemicals in the medicinal plants indicates the presence of disease preventive properties against Myrothecium sp.,